Serverless machine learning with Amazon Redshift : create, train, and deploy machine learning models using familiar SQL commands /: create, train, and deploy machine learning models using familiar SQL commands. (2023) - Panda, Debabrata; Bates, Phil; Pittampally, Bhanu; Joshi, Sumeet
No abstract available